(untitled) (Journal Of Educational and Psychological Researches, 2017)
Supervised By : Prof. dr. Shaker Jaseem Mohammed This research aims to identify the (effectiveness of Bayer’s strategy in the development of deductive thinking among students in the fifth grade literary material European history) and to achieve the goal set researcher null hypothesis of the following: • There is no statistically significant difference between the average scores of the experimental group which studied the use of Bayer’s strategy and the control group, which studied the use of the usual way in the development of deductive reasoning. The study sample consisted of (84 students) of the students in the fifth grade literary breeding Baghdad / Karkh second Directorate for the academic year 2015-2016 were distributed Aanhaldrash Buaq the two groups (43 students) of the experimental group (41 students) of the control group.